2017
DOI: 10.1055/s-0043-119221
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial on the Effects of Vitamin D Supplementation on Metabolic Profiles in Diabetic Hemodialysis

Abstract: The current study was conducted to assess the effects of vitamin D supplementation on insulin metabolism, lipid fractions, biomarkers of inflammation, and oxidative stress in diabetic hemodialysis (HD) patients. This randomized double-blind placebo-controlled clinical trial was carried out among 60 diabetic HD patients. Subjects were randomly allocated into two groups to intake either oral vitamin D3 supplements at a dosage of 50 000 IU (n=30) or placebo (n=30) every 2 weeks for 12 weeks. After 12 weeks of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…At the end of the study period, patients who were treated with vitamin D had significantly decreased serum levels of high-sensitivity CRP and MDA and higher serum TAC levels compared to levels in the placebo group. 150 Compared to the placebo group, the vitamin D group had lower plasma insulin levels and less insulin resistance. Therefore, the authors of the study hypothesized that the beneficial effect of vitamin D therapy might be attributed to the reduced plasma insulin and insulin resistance inhibiting the accumulation of oxidative products linked with poor glycemic control.…”
Section: Vitamin D Analoguesmentioning
confidence: 95%
See 2 more Smart Citations
“…At the end of the study period, patients who were treated with vitamin D had significantly decreased serum levels of high-sensitivity CRP and MDA and higher serum TAC levels compared to levels in the placebo group. 150 Compared to the placebo group, the vitamin D group had lower plasma insulin levels and less insulin resistance. Therefore, the authors of the study hypothesized that the beneficial effect of vitamin D therapy might be attributed to the reduced plasma insulin and insulin resistance inhibiting the accumulation of oxidative products linked with poor glycemic control.…”
Section: Vitamin D Analoguesmentioning
confidence: 95%
“…They were randomized to receive either 50 000 IU of vitamin D3 or matching placebo every 2 weeks for 3 months. At the end of the study period, patients who were treated with vitamin D had significantly decreased serum levels of high‐sensitivity CRP and MDA and higher serum TAC levels compared to levels in the placebo group . Compared to the placebo group, the vitamin D group had lower plasma insulin levels and less insulin resistance.…”
Section: Therapeutic Interventions With Antioxidantsmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have demonstrated that vitamin D intake may reduce the inflammatory response and oxidative stress [6,7]. Therefore, hypovitaminosis D has been suggested to contribute to various metabolic-related conditions including insulin resistance [8], diabetes [9], and CVD [10].…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39][40][41] The Kolmogorov-Smirnov test was used to assess the normality o� the data. [42][43][44][45][46] All subjects in the two groups were classified and analyzed by statistical tests o� the χ 2 , Mann-Whitney and Fridman tests. [47][48][49][50][51][52] In the present study, a P ≤ 0.05 was considered to be significant.…”
Section: Methodsmentioning
confidence: 99%